2020
DOI: 10.1159/000506276
|View full text |Cite
|
Sign up to set email alerts
|

Trimester-Specific Thyroid Function in Pregnant Women with Different Iodine Statuses

Abstract: Objectives: To explore trimester-specific thyroid function changes under different iodine statuses throughout pregnancy. Methods: A cross-sectional study was conducted to assess the pregnancy iodine status, and 2,378 healthy pregnant women covering all 3 trimesters were recruited. Urinary iodine concentration (UIC) was measured by collecting spot urine samples. Blood samples were collected to evaluate thyroid function. Thyroid B-ultrasonography was conducted to measure the thyroid volume (Tvol). Results: The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(57 reference statements)
2
5
0
Order By: Relevance
“…Another study have reported a decreasing trend UIC over the pregnancy [23] . We found maternal TSH levels increased across pregnancy, consistent with the results of a previous study in an iodine su cient area [24] . While another study in an iodine-de cient area [25] reported that no signi cant differences were found regarding the maternal TSH among trimesters.…”
Section: Discussionsupporting
confidence: 92%
“…Another study have reported a decreasing trend UIC over the pregnancy [23] . We found maternal TSH levels increased across pregnancy, consistent with the results of a previous study in an iodine su cient area [24] . While another study in an iodine-de cient area [25] reported that no signi cant differences were found regarding the maternal TSH among trimesters.…”
Section: Discussionsupporting
confidence: 92%
“…6 In few studies there was no correlation of thyroid volume in pregnant females with age. 16,17 We also found a positive correlation of age and thyroid volume though it was insignificant.…”
Section: Anthropometric Factorssupporting
confidence: 51%
“…BMI had shown a positive correlation with thyroid volume during pregnancy. 6,[16][17][18] Also, Elbrashy et al in his study showed BMI as an independent factor affecting thyroid gland volume. 6 Similarly, in our study, on applying linear regression analysis BMI was found to the sole independent predictor of thyroid volume as seen.…”
Section: Anthropometric Factorsmentioning
confidence: 99%
“…The specific mechanism of placental abruption induced by thyroid dysfunction remains unclear. Postpartum hemorrhage is defined as blood loss with related signs or hypovolemic symptoms that occur within 24 hours of delivery, with a blood loss of 1,000 mL or more at 24 hours postpartum (45). The results in this study showed that thyroid dysfunction could increase the incidence of postpartum hemorrhage.…”
Section: Discussionmentioning
confidence: 73%